TECHNICAL CREATIVITY AS A WAY TO OVERCOME STEREOTYPED ACTIVITIES - Доценко, Л. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
Creativity in general and technical creativity in particular is a way out beyond the accepted norms regarding this activity and thus a qualitatively new to creativity in general and technical creativity in particular is a way out beyond the accepted norms regarding this activity and thus a qualitatively new product is not stereotypical. The highest level of technical creativity is innovation